Design of Topical Moxifloxacin Mucoadhesive Nanoemulsion for the Management of Ocular Bacterial Infections - Ahmed Adel Ali Youssef; Ruchi Thakkar; Samir Senapati; Poorva H. Joshi; Narendar Dudhipala; Soumyajit Majumdar (MDPI AG, 2022)
Ocular bacterial infections can lead to serious visual disability without proper treatment. Moxifloxacin (MOX) has been approved by the US Food and Drug Administration as a monotherapy for ocular bacterial infections and is available commercially as an ophthalmic solution (0.5% w/v). However, precorneal retention, drainage, and low bioavailability remain the foremost challenges associated with current commercial eyedrops. With this study, we aimed to design a MOX-loaded nanoemulsion (NE; MOX-NE) with mucoadhesive agents (MOX-NEM) to sustain MOX release, as well as to overcome the potential drawbacks of the current commercial ophthalmic formulation. MOX-NE and MOX-NEM formulations were prepared by hot homogenization coupled with probe sonication technique and subsequently characterized. The lead formulations were further evaluated for in vitro release, ex vivo transcorneal permeation, sterilization, and antimicrobial efficacy studies. Commercial MOX ophthalmic solution was used as a control. The lead formulations showed the desired physicochemical properties and viscosity. All lead formulations showed sustained release profiles a period of more than 12 h. Filtered and autoclaved lead formulations were stable for one month (the last time point tested) under refrigeration and at room temperature. Ex vivo transcorneal permeation studies revealed a 2.1-fold improvement in MOX permeation of the lead MOX-NE formulation compared with Vigamox® eyedrops. However, MOX-NEM formulations showed similar flux and permeability coefficients to those of Vigamox® eyedrops. The lead formulations showed similar in vitro antibacterial activity as the commercial eyedrops and crude drug solution. Therefore, MOX-NE and MOX-NEM formulations could serve as effective delivery vehicles for MOX and could improve treatment outcomes in different ocular bacterial infections.